Number Theory or Geometry?

Every prime p p satisfies p 1 ( m o d 4 ) p\equiv1\pmod4 is a hypotenuse of a right angle triangle with three sides of integer values.

False True Cannot be determined

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kelvin Hong
May 2, 2018

First prove that every prime has the form p 1 ( m o d 4 ) p\equiv1\pmod4 can be expressed as the sum of squares:

Relevant Wiki: Legendre Symbol

Because of Legendre Symbol: ( 1 / p ) = 1 , (-1/p)=1, if p 1 ( m o d 4 ) p\equiv1\pmod4 , we can find an integer a a which is coprime to p p , satisfies a 2 1 ( m o d p ) a^2\equiv-1\pmod p .

Let's first look at this case: a x y ( m o d p ) ax\equiv y\pmod p , there is at least a solution x 0 , y 0 x_0,y_0 which a x 0 y 0 ( m o d p ) ax_0\equiv y_0\pmod p , satisfies 0 < x 0 < p , 0 < y 0 < p 0<\lvert x_0\rvert<\sqrt p,0<\lvert y_0\rvert<\sqrt p (see the proof below). Squaring both side gives x 2 + y 2 0 ( m o d p ) x^2+y^2\equiv0\pmod p , but 0 < x 0 2 + y 0 2 < 2 p 0<x_0^2+y_0^2<2p forced x 2 + y 2 = p x^2+y^2=p .

Next step, by letting q = 2 x y , r = x 2 y 2 q=2xy,r=x^2-y^2 (WLOG, let x > y x>y ), we can yields a triplet of q , r , p q,r,p which are three sides of a right angle triangle with, integer values of side lengths.


The proof:

Consider the set S = { a x y 0 x < p , 0 y < p } S=\{ax-y|0\leq x<\sqrt p,0\leq y<\sqrt p\} , there are exactly ( p + 1 ) 2 > p 2 = p (\lfloor p\rfloor+1)^2>\sqrt p^2=p elements inside that, by Pigeonhole Theorem, at least a pair of integers in the set are congruent modulo p p , says ( x 1 , y 1 ) , ( x 2 , y 2 ) (x_1,y_1),(x_2,y_2) , so a x 1 y 1 a x 2 y 2 ( m o d p ) a ( x 1 x 2 ) y 1 y 2 ( m o d p ) \begin{aligned}ax_1-y_1&\equiv ax_2-y_2\pmod p\\\\a(x_1-x_2)&\equiv y_1-y_2\pmod p\end{aligned} By letting x 0 = x 1 x 2 , y 0 = y 1 y 2 x_0=x_1-x_2,y_0=y_1-y_2 , we conclude that this is the same as a x 0 y 0 ( m o d p ) ax_0\equiv y_0\pmod p , but if x 0 = 0 x_0=0 will cause y 0 = 0 y_0=0 , this says x 1 = x 2 , y 1 = y 2 x_1=x_2,y_1=y_2 , exactly the same element in the set S S , contradict the assumption, this completes the proof.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...